Analisis Karakter Religius Dalam Kitab Ta’liim Al-Muta’allim Karya Imam Al-Zarnuji Dan Implikasinya Terhadap Pendidikan Karakter (Kajian Ilmu Pendidikan Islam) - Salamudin, Ceceng; Alawiyah, Imaroh (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
The moral crisis among students, exemplified by drug abuse, bullying, plagiarism, and sexual violence, necessitates ongoing research by Islamic education scholars into religious texts written by prominent scholars. These studies aim to reinforce the conceptual foundations that can be proposed as solutions to these moral issues. The book "Ta’liim Al-Muta’allim" is a key reference rich in religious values that offers a conceptual alternative for addressing contemporary moral problems. The objective of this research is to describe the religious character values found in "Ta’liim Al-Muta’allim" and their implications for character education. This research falls under the category of library research with a descriptive-analytical method. Data collection involved library research followed by content analysis of the readings. The primary data source was the text of "Ta’liim Al-Muta’allim," supplemented by books, journals, and other written sources relevant to the research goals. The findings indicate that "Ta’liim Al-Muta’allim" contains significant religious character values derived from five main themes: the intention in learning, choosing teachers and friends, revering knowledge and scholars, reliance on Allah (tawakkul), and maintaining piety (wara’) during learning. These religious character values promote compassion, tolerance, and the upholding of religious trust among students. These attitudes are crucial in addressing the character issues faced by students today. Keywords: Religious Character, Character Education, Islamic Educational Philosophy